In silico Design of Laccase Thermostable Mutants From Lacc 6 of Pleurotus Ostreatus - Díaz, Rubén; Díaz-Godínez, Gerardo; Anducho-Reyes, Miguel Angel; Mercado-Flores, Yuridia; Herrera-Zúñiga, Leonardo David (Frontiers in Microbiology, 2018)
Fungal laccase enzymes have a great biotechnological potential for bioremediation processes due to their ability to degrade compounds such as ρ-diphenol, aminophenols, polyphenols, polyamines, and aryldiamines, with a wide range of activity at different pH values, however, high temperatures can cause partial or total loss of enzymatic activity, so it is appropriate to do research to modify the secondary and/or tertiary structure of these enzymes to make them more resistant to extreme temperature conditions. In silico, a structure of the Lacc 6 enzyme of Pleurotus ostreatus was constructed using a laccase of Trametes versicolor as a template. From this structure, 16 mutants with possible resistance at high temperature due to ionic interactions, salt bridges and disulfide bonds were also obtained in silico. It was determined that 12 mutants called 4-DB, 3-DB, D233C-T310C, F468P, 3-SB, L132T, N79D, N372D, P203C, P203V, T147E and W85F, presented the lowest thermodynamic energy. Based on the previous criterion and determining the least flexibility in the protein structures, three mutants (4-DB, 3-DB and P203C) were selected, which may present high stability at high temperatures without affecting their active site. The obtained results allow the understanding of the molecular base that increase the structural stability of the enzyme Lacc 6 of Pleurotus ostreatus, achieving the in silico generation of mutants, which could have activity at high temperatures.